Effects of a low severity prescribed fire on water-soluble elements in ash from a cork oak (Quercus suber) forest located in the northeast of the Iberian Peninsula. (Environmental research, 2011)
Wildfire is the major disturbance in Mediterranean forests. Prescribed fire can be an alternative to reduce the amount of fuel and hence decrease the wildfire risk. However the effects of prescribed fire must be studied, especially on ash properties, because ash is an important nutrient source for ecosystem recovery. The aim of this study is to determine the effects of a low severity prescribed fire on water-soluble elements in ash including pH, electrical conductivity (EC), calcium (Ca), magnesium (Mg), sodium (Na), potassium (K), aluminum (Al), manganese (Mn), iron (Fe), zinc (Zn), silica (SiO(2)) and total sulphur (TS). A prescribed fire was conducted in a cork oak (Quercus suber) (Q.S) forest located in the northeast part of the Iberian Peninsula. Samples were collected from a flat plot of 40×70m mainly composed of Q.S and Quercus robur (Q.R) trees. In order to understand the effects of the prescribed fire on the soluble elements in ash, we conducted our data analysis on three data groups: all samples, only Q.S samples and only Q.R samples. All three sample groups exhibited a significant increase in pH, EC (p<0.001), water-soluble Ca, Mg, Na, SiO(2) and TS and a decrease in water-soluble Mn, Fe and Zn. Differences were identified between oak species for water-soluble K, Al and Fe. In Q.S samples we registered a significant increase in the first two elements p<0.001 and p<0.01, respectively, and a non-significant impact in the third, at p<0.05. In Q.R data we identified a non-significant impact on water-soluble K and Al and a significant decrease in water-soluble Fe (p<0.05). These differences are probably due to vegetation characteristics and burn severity. The fire induced a higher variability in the ash soluble elements, especially in Q.S samples, that at some points burned with higher severity. The increase of pH, EC, Ca, Mg, Na and K will improve soil fertility, mainly in the study area where soils are acidic. The application of this low severity prescribed fire will improve soil nutrient status without causing soil degradation and thus is considered to be a good management strategy.